Geguritan Anggastya; Analisis Struktur dan Fungsi - Okta Era Yati, Ni Made; Agung Mulyawati R, Tjok Istri; Suryati, Ni Made (Humanis; Vol 17 No 3 (2016), 2016)
Research on Anggastya Geguritan is about the analysis of the structure and function. This analysis has the objective to describe the structure and functions contained in the Geguritan Anggastya . This study uses a structural theory and the theory of functions. Based on the structural theory and Teeuw Luxemburg Ratna theory, the theory of functions used Damono theory and Ratna. The methods and techniques used are divided into three stages, namely (1) the methods and techniques used method of providing data reading and recording techniques, which assisted with translation techniques; (2) the method and the data teknikanalisis used qualitative methods and techniques of descriptive analysis; and (3) the methods and data analysis used teknikhasil informal formal methods aided by deductive and inductive techniques. Disclosures of the text structure Anggastya Geguritan structure forms including; code language and literature, a style that include a comparison of style, style convergence and stylistic contradictions. V ariety of language includes Bali Alus language, Bali Madya language and Bali Kasar language . Narrative structure include: the incident, there were seven incidents, using advanced groove and the groove is divided into five stage; stage situation, stage generating circumstances, stage rising action, stage climax and stage denoument ,  character and characterization are divided into three ; the main character, a character secondary, and figures complementary, the background, in Geguritan Anggastya used backlight time, the background of the place, and background ambience, the theme contained in Geguritan Anggastya is karma phala, and the mandate. Functions contained in the Geguritan Anggastya is function as a medium of teaching religion, as a medium of moral education and intellect plant, and as a medium for social development